2022
DOI: 10.3389/fchem.2022.843859
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Electrochemical Performance of PI-5-CA/C-SWCNT Nanohybrid for Sensitive Detection of E. coli O157:H7 From the Real Sample

Abstract: Redox activity is an important indicator for evaluating electrochemical biosensors. In this work, we have successfully polymerized indole-5-carboxylic acid into poly-5-carboxyindole nanomaterials (PI-5-CA), using its superior redox activity, and introduced carboxylated single-walled carbon nanotubes (C-SWCNTs) to synthesize a composite material. Finally, a synthesized composite material was used for the modification of the glass carbon electrode to fabricate the PI-5-CA/C-SWCNTs/GCE-based immunosensor and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…7D). Wang et al [40] prepared an immunosensor to detect E. coli O157:H7, showing a 6.7% decrease in current after 2 weeks. In the present study, the current signal decreased by 4.08% after 2 weeks, which indicated that the prepared immunosensor had good stability.…”
Section: Speci City Repeatability and Stabilitymentioning
confidence: 99%
“…7D). Wang et al [40] prepared an immunosensor to detect E. coli O157:H7, showing a 6.7% decrease in current after 2 weeks. In the present study, the current signal decreased by 4.08% after 2 weeks, which indicated that the prepared immunosensor had good stability.…”
Section: Speci City Repeatability and Stabilitymentioning
confidence: 99%
“… 25 32 Recently, a few groups have already reported the identification of E. coli O 157 :H 7 with a limit of detection (LOD) of as low as 2–10 CFU/mL, but a lower limit of detection is still needed for bacterial analysis in food and clinical samples. 25 , 28 , 33 , 34 …”
Section: Introductionmentioning
confidence: 99%
“…25−32 Recently, a few groups have already reported the identification of E. coli O157:H7 with a limit of detection (LOD) of as low as 2−10 CFU/mL, but a lower limit of detection is still needed for bacterial analysis in food and clinical samples. 25,28,33,34 Subsequently, novel and cost-effective carbon paste electrodes comprising plasma functionalized carbon were fabricated and used as working electrodes. In addition, a robust and costeffective miniaturized E-cell was also engineered to reduce sample wastage and improve the electrochemical reversibility of the electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation